2020
DOI: 10.1021/acs.chemmater.0c01995
|View full text |Cite
|
Sign up to set email alerts
|

Shielded Silver Nanorods for Bioapplications

Abstract: Silver is arguably the best plasmonic material in terms of optical performance. However, wide application of Ag and Ag-containing nanoparticles is usually hindered by two major drawbacks, namely, chemical degradation and cytotoxicity. We report herein a synthetic method for highly monodisperse polymer-coated Ag nanorods, which are thereby protected against external stimuli (oxidation, light, heat) and are noncytotoxic to various cell lines. The monodispersity of Ag nanorods endows them with narrow plasmon band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 53 publications
0
40
0
Order By: Relevance
“…Cytotoxicity and chemical degradation are the two major drawbacks of AgNPs. To overcome these drawbacks, scientists have developed a new synthetic approach for highly monodisperse polymer-coated AgNRs, which are noncytotoxic and protected against external stimuli such as heat, light and oxidation [ 115 ]. A different method of sample preparation is required for each of the characterization techniques.…”
Section: Characterization Of Agnpsmentioning
confidence: 99%
“…Cytotoxicity and chemical degradation are the two major drawbacks of AgNPs. To overcome these drawbacks, scientists have developed a new synthetic approach for highly monodisperse polymer-coated AgNRs, which are noncytotoxic and protected against external stimuli such as heat, light and oxidation [ 115 ]. A different method of sample preparation is required for each of the characterization techniques.…”
Section: Characterization Of Agnpsmentioning
confidence: 99%
“…reported a monodisperse polymer‐coated silver nanorods (AgNRs), which were synthesized through a wet‐chemistry reaction. [ 89 ] Experimental results confirmed that these AgNRs had good optical response and therapeutic efficiency. Beyond that, Swart et al.…”
Section: D Transition Metal–based Nanomaterials With Anisotropic Shape For Biomedical Applicationsmentioning
confidence: 77%
“…[ 87 ] Compared with normal spherical nanoparticles, more advantages of this nanostructure are generally accepted, such as increased ability for cell internalization, high drug loading capacity, and easy functionalization process. [ 88,89 ] Recently, various transition metals, including Bi, Fe, Zn, and so on, have been shaped into nanorod structures.…”
Section: D Transition Metal–based Nanomaterials With Anisotropic Shape For Biomedical Applicationsmentioning
confidence: 99%
“…Apart from the detection of “free” molecules such as biomarkers, SERS can be used like CLSM for live-cell imaging with the help of so-called SERS nanotags. 16 In this case, the plasmonic NPs are decorated with Raman reporter (RaR) molecules. As each RaR will have its unique fingerprint, SERS nanotags can be employed to label different cell types, which can subsequently be imaged with a single laser source, leading to an excellent multiplexing capacity of the technique ( Figure 4 ).…”
Section: Bioink Characterization and Scaffold Testingmentioning
confidence: 99%
“…Likewise, multiplexing is feasible with either of the aforementioned techniques, highlighting their versatility. Adapted from ref ( 16 ). Copyright 2020 American Chemical Society, and ref ( 17 ).…”
Section: Bioink Characterization and Scaffold Testingmentioning
confidence: 99%